Wolfgang Köhler and Hans Geitel: correspondence 1907-1920 - Zeidler, Włodzisław (Studia Psychologica: Theoria et praxis, 2011)
The author of presented article suppose that a correspondence between psychologists belongs to documents which create history of psychology. Especially, when a history is treated as a social history, and letters comprise not only private matters but concern both scientific and political problems. The correspondence between Einstein and Freud go away the bounds of psychology as a science and indicate on its meaning. The correspondences between Wundt and Kraepelin, between Stern and von Meinong, between Stern and Jonas Cohn bring nearer opinions and problems of arising psychology and in the same time appear friendly and fully comprehensive contacts between the authors of these letters. The letters of Wolfgang Kohler to Hans Geitel are multifaceted document. They comprise comments on research program realized in Teneriffa. One can find in them peculiar introducing to postdoctoral dissertation of Wolfgang Kohler, which essence is still very difficult and unintelligible for many psychologists.